PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT MELATI SOEROZA INDAH PERDANA - Elronny Elronny; Hairudinor Hairudinor; Muhammad Riduansyah Syafari (Universitas Lambung Mangkurat, 2021)
This study aims to examine the effect of Transformational Leadership (X1) and Compensation (X2) on Employee Performance (Y) at PT. Melati Soeroza Indah Perdana located in North Barito Regency, Central Kalimantan Province. Samples were taken as many as 54 employees using saturated sampling techniques. Data collection uses a questionnaire while data analysis uses Multiple Linear Regression Analysis.The test results prove Transformational Leadership (X1) has a significant effect on performance with a large effect of 34.88%, Compensation (X2) has a significant effect on Employee Performance (Y). Simultaneously the Transformational Leadership (X1) and Compensation (X2) variables have a significant effect on Employee Performance (Y) with a large effect of 24.81%.Keywords: Transformational Leadership, Compensation, Job Satisfaction and Employee performance